An empirical study on the risk management strategies IT outsourcing in Malaysia public sector - Ahlan, Abdul Rahman; Arshad, Yusri; Syed Ibrahim, Sharifah Norhafiza (2012)
The complexities of IT outsourcing (ITO) projects require an emphasis on proper and effective project risk management strategies adopted by both service receivers and providers. Literature indicates that an alarming number of mega-deal ITO deals failed due to many reasons. For instance, ill-planned and poorly-managed projects, large and multifaceted projects are more risky and contextual issues are highly influential. In addition, in more complex project commissioning and development where political and organisational elements come to the fore further aggravates the need for proper risk managements. Moreover, an informed selection of an adequate pricing model indeed plays a crucial, if not decisive, role to ensure a successful deal outcome and to mitigate risks in the wake of the deal. Above all, the private versus public paradigms delineate borders on the needed priorities that require appropriate strategies to be adopted suitable in each environment and circumstances. Literature shows that this risk management strategy in ITO area is still under-researched and therefore provides a gap for future research. This study attempts to fill in this void. In this study, we adopt a qualitative case study approach to investigate on the ITO project success experiences from five public sector agencies. Content analysis was used to analyse available documents and in-depth semi-structured interview feedbacks. The study finds the agencies have applied ITO guidelines recommended by Malaysia public sector IT modernisation and administrative planning unit. Moreover, the project management approaches and standards adopted were different among project managers. However, the formal and informal communication channels were used in all cases to enhance the relationship between all stakeholders. Nevertheless, the SP adopted methodologies and standards were either internally developed or well recognised project management methodologies in the five projects. Finally, the study contributes by filling up the literature gap and providing empirical evidence on ITO risk and risk management strategies adopted in the public healthcare sector.